Conversion of cellulosic waste materials into nanostructured ceramics and nanocomposites - Pang, Suh Cem; Chin, Suk Fun; Yih, Victor (VBRI press, 2011)
Cellulosic waste materials which include sawdust, wastepaper, corncob and sugarcane bagasse were converted into nanostructured ceramics and nanocomposites by submersion in silica colloidal suspension (sol) and subsequently by calcination of the cellulosic/SiO2 nanocomposites under controlled conditions. Depending on the calcination conditions used,nanostructured SiO2 ceramics and carbon/SiO2 nanocomposites were obtained. The morphology of resulting nanostructured ceramics and nanocomposites obtained from four types of cellulosic waste materials were characterized by Scanning Electron Microscopy (SEM), Fourier transformed infrared spectroscopy (FTIR), and CHN elemental analyzer. The effect of cellulosic materials on the properties of nanostructured ceramics and nanocomposites formed were investigated.